(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Guidelines have been shown to improve cancer care by standardizing care. In resource- limited settings where there is a consistent increase in disease burden, we need to use finite resources well to ensure adequate care is provided nationwide. In 2016, the African Cancer Coalition was established as a regional collaboration to develop comprehensive standard cancer treatment guidelines tailored to sub–Saharan Africa. Cancer experts from African countries collaborated with the National Comprehensive Cancer Network (NCCN) and the American Cancer Society through a series of organized meetings to harmonize cancer treatment guidelines. To date, all gynecologic malignancies have been reviewed and updated on the website. These resource-stratified guidelines are not intended to lower the bar for cancer care in resource-limited settings, but to use resources adequately in already constrained settings. Objectives 1. Educate members on how to use the harmonized guidelines. 2. Use of the guidelines as an educational tool for gynecologic oncology fellowship programs in Kenya. 3. Access the wider obstetric and gynecology fraternity to ensure appropriate use of finite resources and to avoid multiple tests before referring patients for care by the gynecologic oncologist. 4. Compare the harmonized guidelines to the Kenya national guidelines.